A preliminary study of gene expression changes in Koalas Infected with Koala Retrovirus (KoRV) and identification of potential biomarkers for KoRV pathogenesis - Lipi Akter; Md Abul Hashem; Mohammad Enamul Hoque Kayesh; Md Arju Hossain; Fumie Maetani; Rupaly Akhter; Kazi Anowar Hossain; Md Haroon Or Rashid; Hiroko Sakurai; Takayuki Asai; M. Nazmul Hoque; Kyoko Tsukiyama-Kohara (BMC Veterinary Research)
Abstract Background Koala retrovirus (KoRV), a major pathogen of koalas, exists in both endogenous (KoRV-A) and exogenous forms (KoRV-A to I and K to M) and causes multiple disease phenotypes, including carcinomas and immunosuppression. However, the direct association between the different KoRV subtypes and carcinogenesis remains unknown. Differentially expressed gene (DEG) analysis of peripheral blood mononuclear cells (PBMCs) of koalas carrying both endogenous (KoRV-A) and exogenous (KoRV-A, B, and C) subtypes was performed using a high-throughput RNA-seq approach. PBMCs were obtained from three healthy koalas: one infected with endogenous (KoRV-A; Group I) and two infected with exogenous (KoRV-B and/or KoRV-C; Group II) subtypes. Additionally, spleen samples (n = 6) from six KoRV-infected deceased koalas (K1- K6) and blood samples (n = 1) from a live koala (K7) were collected and examined to validate the findings. Results All koalas were positive for the endogenous KoRV-A subtype, and eight koalas were positive for KoRV-B and/or KoRV-C. Transcription of KoRV gag, pol, and env genes was detected in all koalas. Upregulation of cytokine and immunosuppressive genes was observed in koalas infected with KoRV-B or KoRV-B and -C subtypes, compared to koalas infected with only KoRV-A. We found 550 DEG signatures with significant (absolute p < 0.05, and absolute log2 Fold Change (FC) > 1.5) dysregulation, out of which 77.6% and 22.4% DEGs were upregulated (log2FC > 1.5) and downregulated (log2FC <  − 1.5), and downregulated (log2 FC <  − 1), respectively. We identified 17 unique hub genes (82.3% upregulated and 17.7% down-regulated), with KIF23, CCNB2, POLR3F, and RSL24D1 detected as the potential hub genes modified with KoRV infection. Real-time RT-qPCR was performed on seven koalas to ascertain the expression levels of four potential hub genes, which were subsequently normalized to actin copies. Notably, all seven koalas exhibited distinct expression signatures for the hub genes, especially, KIF23 and CCNB2 show the highest expression in healthy koala PBMC, and POLR3F shows the highest expression in koala with lymphoma (K1). Conclusion Thus, it can be concluded that multiple KoRV subtypes affect disease progression in koalas and that the predicted hub genes could be promising prognostic biomarkers for pathogenesis.